Crown Lengthening for Obtaining Biological Width in Dental Restoration: A Case Report - Ilham Hutomo, Dimas; Sunarto, Hari; Ramadianti Fitria, Adinda (KnE Medicine, 2022)
Background: Biological width is a natural defensive space for periodontal tissue which is important for maintaining healthy periodontal tissue so that it can support the success of dental restoration treatment. The localized alveolar bone loss, gingival recession, localized gingival hyperplasia or a combination of all three can be caused by poor biological width restoration. Biological width is obtained through crown lengthening when restoration of teeth have caries or subgingival fractures under the gingival attachment. The crown-lengthening procedure is performed to increase the height of the clinical crown for restoring and improving the esthetics of the teeth. Objective: This case report presents two cases of crown lengthening with osteotomy before the dental restoration procedure. Case Report: The first case was of a 43-year-old woman who was referred from the prosthodontics clinic RSKGM FKG UI before making permanent restorations on tooth 13. Clinical examination showed red gums, swelling and caries that extended to subgingival especially in the distal part. A crown-lengthening procedure with an osteotomy was performed distally to increase the height of the clinical crown so that it had a good ferrule effect for the restoration of the tooth. The second case was of a 25-year-old female patient who had undergone root canal treatment by a general dentist. The clinical appearance of the tooth showed an imbalance in the height of the gingival zenith with the tooth next to it, and the clinical crown looked short. Crown lengthening with osteotomy was done to get a balanced zenith height. Conclusion: Crown lengthening is a periodontal surgical treatment performed to obtain optimum biological width to support tooth restoration. Keywords: crown lengthening, osteotomy, biological width